2021
DOI: 10.1186/s13071-021-04865-5
|View full text |Cite
|
Sign up to set email alerts
|

Giardia duodenalis extracellular vesicles regulate the proinflammatory immune response in mouse macrophages in vitro via the MAPK, AKT and NF-κB pathways

Abstract: Background Giardia duodenalis is an extracellular protozoan parasite that causes giardiasis in mammals. The presentation of giardiasis ranges from asymptomatic to severe diarrhea, and the World Health Organization lists it in the Neglected Diseases Initiative. Extracellular vesicles (EVs) are a key mediator of intracellular communication. Although previous studies have shown that G. intestinalis can regulate a host’s innate immune response, the role of G. intestinalis EVs (GEVs) in triggering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
(51 reference statements)
1
23
0
Order By: Relevance
“…It has been reported that giardial multicellular vesicles (MVs) are absorbed by dendritic cells, resulting in increased allostimulation ( Evans-Osses et al., 2017 ). In other reports, EVs released by Giardia have been shown to affect the TLR2 and NLRP3 inflammasome pathways and proinflammatory immune responses in mouse macrophages via the MAPK, AKT, and NF-κB pathways ( Zhao et al., 2021a ; Zhao et al., 2021b ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…It has been reported that giardial multicellular vesicles (MVs) are absorbed by dendritic cells, resulting in increased allostimulation ( Evans-Osses et al., 2017 ). In other reports, EVs released by Giardia have been shown to affect the TLR2 and NLRP3 inflammasome pathways and proinflammatory immune responses in mouse macrophages via the MAPK, AKT, and NF-κB pathways ( Zhao et al., 2021a ; Zhao et al., 2021b ).…”
Section: Discussionmentioning
confidence: 91%
“…In recent years, efforts have been made to understand the roles of giardial extracellular vesicles (GEVs) in modulating the host immune system ( Zhao et al., 2021a ; Zhao et al., 2021b ). There are three types of extracellular vesicles (EVs), each emanating from different cellular sites including the plasma membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that Giardia infection can enhance the production of proinflammatory cytokines, such as TNF-α, IFN-γ, IL-6, and IL-12 p40 in PMs, through the TLR2-mediated activation of MAPK signaling [ 13 ]. A recent study found that Giardia EVs trigger IL-1β, IL-6, and TNF-α secretion from mouse PMs via promoting the nuclear translocation of the NF-κB p65 subunit [ 53 ]. Another recent study identified TLR2 as a mediator for pyroptotic signaling in mouse PMs induced by Giardia EVs [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the study, the roles played by the MAPK and AKT signaling pathways in EV-induced proinflammatory cytokine production were examined. After inoculating EVs into mouse macrophages, protein phosphorylation in the MAPK and AKT signaling pathways was detected at different times (Zhao et al, 2021b). The results showed that the level of p38 phosphorylation peaked 2 h after EV inoculation and began to decrease 4 h after inoculation.…”
Section: Effects Of Extracellular Vesicles On Giardiasismentioning
confidence: 99%